Historical syntax and linguistic theory - Crisma, Paola; Longobardi, Giuseppe (Oxford : Oxford University Press, 2009)
This text of new work by leading international scholars considers developments in the study of historical linguistics and grammatical theory. It then tests their value and applicability by examining diachronic transmission of syntax at different times and in a wide range of languages.
"The articles contained in this volume were all presented, with the exception of Chapter 1, at the 9th DiGS conference held at the University of Trieste in June 2006"--Foreword.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Syntax; Historical linguistics